Development of biopolymeric-based microneedles for application in drug administration and interstitial fluid extraction - Fonseca, Daniela Filipa da Silva (2021)
Microneedles are arrays comprised of small needle-like projections, of micronsized dimensions. Microneedles were first conceptualized aiming to enable the transdermal administration of drugs and combining the advantages of subcutaneous injections with the simplicity of transdermal patches. These micron-sized structures disrupt the stratum corneum, creating transitory pores which facilitate drug permeation through skin, in a minimally invasive and painless way. Furthermore, by contacting with the upper dermis, the microneedles enable interstitial fluid absorption for analysis of metabolites. In particular, in the last few decades, the use of biopolymers to fabricate microneedles has gained much interest due to their biocompatibility, biodegradability and biomimetic features. Proper consideration needs to be placed onto the sustainable character of these biomaterials and the need to pursue environmentally sustainable practices. Hence, this work aims at studying the preparation, evaluation and application of innovative microneedles systems using biopolymers, namely polysaccharides and proteins, to answer to the need for developing biomaterials of high performance with reduced environmental impact. The first chapter gives a general introduction to the characteristics and properties of microneedles, followed by an overview of biopolymeric microneedles, focusing on their properties and applications. The second chapter of this thesis is focused on the development of microneedles for point-of-care diagnostics, using methacryloyl gelatin (10% (w/v)). These microneedles have high swelling ability, which allows interstitial skin fluid absorption that is afterwards extracted and used for analysis of metabolites. To infer about the diagnostic potential, an agarose in vitro system was employed for urea extraction as a model analyte. Two different concentrations were tested, to mimic a health and (renal) disease state, and it was concluded that >98% analyte was recovered. In this sense, the cytocompatibility of this material coupled with the fluid uptake ability supports the application of methacryloyl gelatin microneedles as a diagnostic tool, offering a promising alternative in this era of point of care diagnostics. Aiming at developing new platforms for drug administration, the third chapter of this thesis describes the preparation and characterization of pullulan microneedles, using 6, 9, 12, 15, 18 e 24% (w/v) of polymer solutions. These presented a regular and uniform geometry and the microneedles prepared with 24% (w/v) pullulan were selected for insulin incorporation and evaluation of the functional properties. The insulin-loaded pullulan microneedles presented a regular morphology and 500 μm in length, mechanically strong to insert human skin ex vivo, creating pores up to 381 μm depth. The conformational stability of insulin into the pullulan system was confirmed through circular dichroism, during one month of storage at 4, 20 and 40 ºC. Therefore, it was possible to highlight the ability of pullulan microneedles to store and deliver this therapeutic agent with no need of cold chain monitoring. In the fourth chapter, the potential of bacterial nanocellulose as a mechanical reinforcement and macromolecular support for the incorporation of bioactive compounds (rutin) was studied using hyaluronic acid (5% (w/v)) microneedles for cosmetics. The antioxidant activity of this phenolic was kept for six months storage of microneedles at room temperature in the dark. Rutin permeation was evaluated using Franz cells and pig skin samples. In addition, the safety of the model system incorporating only bacterial cellulose and hyaluronic acid was evaluated by 13 human volunteers. Redness, erythema and transepidermal water loss in volunteer’s skin were evaluated and no statistical differences were found between the control and the application site, confirming the safety of the system. In a different perspective, the fifth chapter focuses on the preliminary evaluation of gelatin and pectin microneedles for curcumin incorporation, envisioning their potential application in melanoma treatment. The preparation of gelatin-pectin microneedles is described, aiming to evaluate the impact of the polymeric composition on the morphology and mechanical performance. Microneedles prepared with 75% gelatin and 25% pectin were selected for the incorporation of curcumin. Cell viability of three melanoma cell lines was evaluated for different curcumin concentrations, to study the dose-response curve. At this stage, it was defined an IC50 for each cell line and defined the amount of 10 μg curcumin to incorporate into the microneedles systems. Preliminary evaluation highlights the potential for curcumin incorporation into these biopolymeric microneedles and its application as candidates for melanoma treatment. In conclusion, this PhD thesis reported the development of several innovative and functional biopolymeric microneedles systems. The outstanding versatility of biopolymeric microneedles, enabled the development of systems guided for the administration of bioactive compounds, namely insulin, rutin and curcumin. These systems proved to retain the bioactives’ biological activity and the microneedles mechanical stability. The intumescent character of methacryloyl gelatin revealed their potential as a diagnostic tool, which represents a significant step in diagnostics and monitoring of healthcare state, especially for emergent and chronic diseases.